Implementation of Integrated Health Service and Promotion Posts for Non-Communicable Diseases (NCDs) to Improve Knowledge, Anthropometric and Nutritional Counseling Skills of Adolescent Cadres in Schools - Sri Noor Mintarsih; Susi Tursilowati; Ria Ambarwati; Mardiana Mardiana; Zuhria Ismawanti (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2024)
Non-communicable diseases (NCDs) risk factors include changes in the lifestyle of adolescents with unhealthy diets tend to fast food, lack of activity and exercise, increased stressors, and exposure to environmental conditions that are not conducive to health. Establishing NCDs Integrated Health Service and Promotion Post is an efficient and effective control strategy aiming at early detection of NCDs risk factors. Empowerment of peer counsellors as Integrated Development Post cadres is expected to become agents of change and detect NCDs risk factors in schools. This research determines the effectiveness of implementing an adolescent-Integrated Development Post in schools to increase the adolescent cadre’s knowledge, anthropometric skills, and nutritional counseling. It is an experimental design with one group pre-post test at one of the high schools in Semarang City. Integrated Development Post cadres are peer counselors selected according to the criteria of 10% of the total number of students (36 people) from 11th grade. Differences in knowledge scores, anthropometric skills, and nutritional counseling of cadres were analyzed using the Paired T-test. The cadre’s knowledge scores increased from 50.55 to 70.11; anthropometric skills include weighing from 61.67 to 98.98, measuring height from 54.63 to 94.25, and nutritional counseling from 72.92 to 86.71. Paired T-test results show a p-value < 0.05. Integrated Development Post effectively increases cadre’s knowledge scores, anthropometric skills, and nutritional counseling. It can also detect risk factors to prevent and control NCDs in the school.